Astaxanthin formation in Haematococcus pluvialis - Gunnur Sveinsdóttir 1980- (2017)
Verkefnið er lokað til 30.4.2137. Astaxanthin is a high value metabolite from the common algae Haematococcus pluvialis. Astaxanthin is a keto-carotenoid that is commonly used in synthetic form as supplementary feed in fish farming and as a colorant. Astaxanthin is a very powerful anti-oxidant and has many potential health benefits so there is great interest in producing naturally sourced astaxanthin from H. pluvialis to sell as a dietary supplement for human consumption. KeyNatura in Hafnarfjörður is a new company that aims to sell high quality natural astaxanthin from unmodified strains of H. pluvialis. The process for growing and extracting astaxanthin from H. pluvialis has to be optimized and streamlined in order to minimize loss between processing steps and the highest yielding strain must be found. First, three strains of H. pluvialis were cultured under the same conditions in order to find the best performing strain, focusing on growth rate and astaxanthin accumulation. Second, every step of growth and extraction was put to the test so that the loss of astaxanthin product could be determined at each processing step. Some stages of extraction were found to be in need of improvement, in particular drying and supercritical fluid extraction. The information gained from these investigations can be used to determine where adjustments need to made and suggestions proposed on how to potentially improve the process. Astaxanthin er verðmætt fæðubótarefni sem unnið er úr smáþörungnum Haematococcus pluvialis. Astaxanthin er keto-karoteníð sem er oftast notað synthetískt sem viðbót í fiskifóður og sem litarefni. Astaxanthin er mjög kröftugt andoxunarefni sem hefur margvíslega heilsubætandi eiginleika. Það er því mikill áhugi fyrir því að framleiða astaxanthin úr náttúrulegu hráefni, þ.e. H. pluvialis, til neyslu. KeyNatura í Hafnarfirði er nýstofnað fyrirtæki sem hefur að markmiði að selja náttúrulegt, hágæða astaxanthin úr óerfðabreyttum stofni H. pluvialis til manneldis. Frá því að rækta smáþörunginn og vinna úr ...